Myocardial Mechanics in Hypertensive Disorders of Pregnancy: a Systematic Review and Meta-Analysis. Issue 2 (17th November 2021) - O'Driscoll, Jamie M.; Giorgione, Veronica; Edwards, Jamie J.; Wiles, Jonathan D.; Sharma, Rajan; Thilaganathan, Baskaran
Abstract : Supplemental Digital Content is available in the text. Abstract : Global longitudinal strain (GLS) is becoming routinely used to direct the medical management of various cardiac diseases, but its application in pregnancy is unclear. Our objective was to perform a meta-analysis and pool multiple study data to consolidate the evidence base for the role of GLS in the assessment of women with hypertensive disorders of pregnancy (HDP). Electronic database searches were performed in PubMed/Medline and EMBASE for research articles reporting GLS in pregnancies complicated by HDP and normotensive pregnancies that have been published up to September 2021. The meta-analysis included 17 studies with a pooled sample size of 1723 participants, which included 951 women with HDP, of which 680 were preeclamptic, and 772 controls. The primary random-effects pooled analysis demonstrated a statistically significant weighted mean difference in GLS between the HDP and control group (mean difference: 3.08% [CI, 2.33–3.82], P <0.001). When analyzed including only preeclamptic studies, there was also a statistically significant mean difference (mean difference: 2.98% [95% CI, 1.97–3.99], P <0.001). This meta-analysis demonstrates that HDP is associated with greater cardiac maladaptation, evidenced by a significantly reduced GLS compared with normal pregnancy. Echocardiography should be considered as a screening tool in women with HDP to enable early cardiovascular risk prevention through national initiatives.